The Effect of Domperidone Toward Breast Milk Production on Sectio Caesarea Mother - Sri Dinengsih; Cholisah Suralaga (Alma Ata University Press, 2020)
Mothers that give birth with section caesaria (SC) often experience difficulty to get a adequate breast milk production. Various kinds of effort have been conducted to overcome this problem, including pharmacological intervention. One of the medicines that could be possibly used is domperidon. Domperidon is an antagonist receptor of peripheral dopamine that works by choking inhibition effect of prolactin secretion facilitated by dopamine to improve breast milk production.The research aimed to unveil the effect of domperidon toward breast milk production on mother that give birth with SC in Indonesia. This is a quasi-experiment research with two groups post-test only design. The sample of this research 30 were post sectio caesarea patients consisting of 15 patients in intervention group and 15 patients in control group. Purposive sampling was used in the research to get the samples. The instrument used was observation sheets. Result analysis was conducted by calculating the frequency distribution and bivariate analysis with Mann Whitney test. The average score of breast milk production among post-SC mother in the intervention group was 22,60, while the average score of breast milk production among post-SC mother in control group was 15,47, Asymp. value Sig (2 tailed) 0,020 (0,020 < 0,05). Domperidone has been approved to have a significant effect to improve breast milk production on post-SC mothers. Improving breast milk production could be conducted non-pharmacologically, but pharmacological therapy could also be considered if the non-pharmacological therapy doesn’t work well in improving breast milk production.